Willa of the wood - Beatty, Robert, 1963- (Disney-Hyperion, 2018)
In the late 1800s, a twelve-year-old nightspirit living in the Great Smoky Mountains despairs as homesteaders destroy her forest habitat, until a chance encounter with a "day-folk" man changes everything she thought she knew about her people--and their greatest enemy.